Stimulation of PPARα normalizes the skin lipid ratio and improves the skin barrier of normal and filaggrin deficient reconstructed skin - Wallmeyer, Leonie; Lehnen, Dominika; Eger, Natascha; Sochorová, Michaela; Opálka, Lukáš; Kováčik, Andrej; Vávrová, Kateřina; Hedtrich, Sarah (Journal of dermatological science, 2015)
BACKGROUND: Therapeutic options for atopic dermatitis mostly address the symptoms but causal therapies are still missing. Peroxisome proliferator activated receptor (PPAR) agonists exert beneficial effects in patients suffering this disease, whereas the stimulation of PPARα and γ seemed most promising. OBJECTIVES: To elucidate the effects of the PPARα specific agonist WY14643, the PPARγ agonist ciglitazone, and the dual PPARα+γ agonist docosahexaenoic acid (DHA) on the homeostasis and barrier function of filaggrin deficient skin. METHODS: The effects of the PPAR agonists on skin differentiation were evaluated via qPCR, Western blot, histological or immunofluorescence staining. Skin lipid organization was determined by ATR-FTIR and lipid composition was analyzed by HPTLC. Ultimately, the skin barrier function was assessed by skin absorption studies using the radioactively labeled compound testosterone. RESULTS: Significant upregulation of filaggrin after DHA and WY14643 supplementation, but no effect of ciglitazone, on protein and mRNA level was detected. DHA and WY14643, but not ciglitazone, normalized the molar ratio of the main skin barrier lipids to 1:1:1 (free fatty acids:ceramides:cholesterol). Furthermore, DHA and WY14643 supplementation normalized the skin lipid profile in filaggrin deficient skin, but only WY14643 significantly improved the skin barrier function. CONCLUSION: Supplementation particularly with the PPARα agonist WY14643 improved the homeostasis and barrier function of filaggrin deficient skin models by normalization of the free fatty acid profile underlining the potential of PPAR agonists for the treatment of filaggrin-associated skin diseases.
Keywords: metabolismus lipidů; signální transdukce; Membrane Proteins; Signal Transduction; Filaggrin Proteins; kyseliny mastné neesterifikované; Skin lipids; kyseliny dokosahexaenové; Humans; Intermediate Filament Proteins; kožní absorpce; pyrimidiny; permeabilita; Lipid Metabolism; Permeability; Skin; PPAR alpha; kůže; Phenotype; Filaggrin deficiency; Genotype; lidé; Skin barrier recovery; proteiny intermediálních filament; Cells, Cultured; časové faktory; transfekce; Docosahexaenoic Acids; Testosterone; Reconstructed skin models; fenotyp; kultivované buňky; Thiazolidinediones; PPAR agonists; Skin Absorption; RNA Interference; Fatty Acids, Nonesterified; filagriny; membránové proteiny; PPAR gama; genotyp; Transfection; fibroblasty; thiazolidindiony; PPAR alfa; Pyrimidines; Protein Precursors; proteinové prekurzory; testosteron; RNA interference; Time Factors; PPAR gamma; Fibroblasts